Damascius' Philosophy of Time - Golitsis, Pantelis (CHRONOI, 2023)
The late Platonist philosopher Damascius both resumed and rejuvenated the long Greek thinking about time. In distinguishing between different takes on time, he offered novel perspectives, which can be seen as anticipating modern and contemporary theories about time. The greatest merit of his philosophy of time, however, is his deep reflection on what it is for a living being to have its being in becoming and how this relates to temporality.